Development of Memory Structures for Homographs Using Pathfinder Network Representations - Nievas, Francisco; Justicia, Fernando (The Spanish Journal of Psychology, 2003)
Some studies with children have shown that there is no semantic priming at short stimulus onset asynchrony (SOA) in lexical decision and naming tasks for homographs. The predictions of spreading activation theories might explain this missing effect. There may be differences in children’s and adults’ memory structures. We have explored this hypothesis. The development of memory structure representations for homographs was measured by a Pathfinder algorithm. In Experiment 1, the three dependent variables were: the number of links in the network, closeness measures (C), and distances between nodes. Results revealed developmental differences in network structure representations in adults and children. In Experiment 2, results revealed that these differences were not due to the cohort effect. In Experiment 3, the relationship between associative strength, as measured by associative norms, and distances, as measured by Pathfinder algorithm, was explored. The results of these three experiments and empirical research from semantic priming experiments show that these differences in memory structure representations could be one of the sources of the missing semantic priming effect in children.